The Puzzle of Patient Safety: Which Is Better, Criminal Sanctions or a Professional Peer Review Committee Seeking the Truth? - HIGUCHI, Norio (Nihon Rinshō Masui Gakkai shi, 2008)
Traditional legal responses to medical accidents with negligence are punitive in nature towards physicians and other medical professionals. Negligent physicians are subject to the threat of criminal prosecution, disciplinary proceedings, and civil liability. The use of criminal sanctions, in particular, has been prevalent in recent years. This increase is, however, under severe criticism after a decade of many experiences. Although the medical profession once accepted intervention by the police and prosecutors, they have begun to realize that the puzzle of patient safety could not be solved by this procedure. That is why major academic societies of physicians started the so-called model project in 2005 with the support of the Ministry of Health and Welfare, in which they themselves have tried to seek out the true cause of medical mishaps and the effective way of preventing similar accidents. Currently our government is making a proposal to establish a committee for patient safety. This move makes us reconsider what is the proper role of the law in improving safety in the clinical setting.